Quail Response to Two Large-Scale Wildfires in the Texas Panhandle - Kenneth A. Cearley; Dale Rollins; Brandon Wilson (National Quail Symposium Proceedings, 2017)
Rangeland wildfires burned 275,805 ha in 2 large blocks in the Texas Panhandle in March 2006. We assessed the impact on northern bobwhite (Colinus virginianus) and scaled quail (Callipepla squamata) populations through use of spring call-counts at 6 study sites during summer 2006–2008. Call-counts were higher in 2006 on non-burned (control) sites combined than on burned sites combined. Two years post-burn call-counts were higher on 3 of the burned sites and on 3 of the control sites. Between year comparisons revealed a difference only in the 2006/2007 pairing with 2006 having lower counts on burned than on control sites. Vegetation regrowth and concomitant quail abundance was affected more by soil texture, topography, and precipitation than spatial relation to the burn perimeter. Sites comprised of coarse-textured soils responded more quickly and likely supported higher densities pre-burn than sites with more finely-textured soils. Shortgrass sites without a significant woody component probably had lower populations pre-burn, and recovered more slowly than mid-grass communities that had a greater woody component. Landscape relief appeared to mitigate the immediate impact of the burn, enhancing recovery by providing refugia (unburned patches) within the burn.
Keywords: Callipepla squamata; Colinus virginianus; fire; northern bobwhite; scaled quail; Texas Panhandle; wildfire